2019
DOI: 10.3357/amhp.5236.2019
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Fatigue Among Airline Crew During 4 Consecutive Days of Flight Duty

Abstract: BACKGROUND: Airline crew are being exposed to extended workdays and compressed work periods, with quick returns between duties, implying a heightened physiological and psychological strain that may lead to sleep deprivation and fatigue. The aim of the study was assessment of the effect of an extended day of flight duty and a compressed work week with regard to recovery, cumulative fatigue, and neurobehavioral performance.METHODS: We followed 18 pilots and 41 cabin crewmembers during four consecutive days of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
7

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 0 publications
2
26
0
7
Order By: Relevance
“…Some support is found in the study by Goffeng et al. (2019), which did not find any change in Samn‐Perelli fatigue scores or reaction time after 4 days of around 40 h of duty time. On the other hand, the same study found an impairment in reaction time performance with a higher number of sectors during the four‐duty day period (range 10–20 sectors).…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Some support is found in the study by Goffeng et al. (2019), which did not find any change in Samn‐Perelli fatigue scores or reaction time after 4 days of around 40 h of duty time. On the other hand, the same study found an impairment in reaction time performance with a higher number of sectors during the four‐duty day period (range 10–20 sectors).…”
Section: Discussionmentioning
confidence: 62%
“…Despite the absence of previous work on cumulative effects on fatigue, the lack of association (Table 4, model 1) between fatigue and accumulation of duty time, number of sectors and block time was somewhat unexpected. Some support is found in the study by Goffeng et al (2019), which did not find any change in Samn-Perelli fatigue scores or reaction time after 4 days of around 40 h of duty time. On the other hand, the same study found an impairment in reaction time performance with a higher number of sectors during the four-duty day period (range 10-20 sectors).…”
Section: Accumulation Of Fatigue During the 7-day Work Periodmentioning
confidence: 67%
See 3 more Smart Citations